Fulfillment of Local Content in The Era of Democratization And Digitalization In West Java - Ahsani Taqwim Aminuddin; Tryan Nugraha (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2026)
This study examines how networked broadcasters in West Java, Indonesia, implement a national policy mandating a minimum of 10% local content. Drawing on in-depth interviews with editorial, production, and managerial staff, combined with regulatory data, the study analyzes production and distribution practices through a political economy of communication perspective, focusing on structuration, commodification, and spatialization. The findings reveal that most